An investigation on the impact of environment factors as constraints on Libyan commercial adoption of Islamic financial transactions using the Neo-Institutional Theory - Salwa Abdel Gader Khalleefah, Bin Idrees; Alhabshi, Syed Musa; Ashurov, Sharofiddin; Anwar Hasan, Abdullah Othman (2021)
This paper highlights the Libyan commercial banks’ institutional environment, as institutional constraints on their adoption of Islamic financial transactions. Principally, in the context of formal and informal constraints, the article investigates Libyan commercial banks' external institutional environment that governs their behavior and decisions. To achieve this end, the authors employed reports of the Libyan Central Bank, local, international reports, and semi-structured interviews. Finally, it reviews the implications to investigate the institutional environment and the study result conducted about Libyan commercial banks. Highlighting the research gap as a future study opens up new horizons to research the effect of the external environment on the commercial banks ' adoption of Islamic financial transactions. Specifically, providing a framework that includes the influence of all main actors that openly determine the commercial banks' organizational behavior rather than the only influence of bank's users.